Counteraction of Oxidative Stress by Vitamin E Affects Epigenetic Regulation by Increasing Global Methylation and Gene Expression of MLH1 and DNMT1 Dose Dependently in Caco-2 Cells. (22nd March 2018) - Zappe, Katja; Pointner, Angelika; Switzeny, Olivier J.; Magnet, Ulrich; Tomeva, Elena; Heller, Jutta; Mare, George; Wagner, Karl-Heinz; Knasmueller, Siegfried; Haslberger, Alexander G.
Abstract : Obesity- or diabetes-induced oxidative stress is discussed as a major risk factor for DNA damage. Vitamin E and many polyphenols exhibit antioxidative activities with consequences on epigenetic regulation of inflammation and DNA repair. The present study investigated the counteraction of oxidative stress by vitamin E in the colorectal cancer cell line Caco-2 under normal (1 g/l) and high (4.5 g/l) glucose cell culture condition. Malondialdehyde (MDA) as a surrogate marker of lipid peroxidation and reactive oxygen species (ROS) was analyzed. Gene expression and promoter methylation of the DNA repair gene MutL homolog 1 ( MLH1 ) and the DNA methyltransferase 1 ( DNMT1 ) as well as global methylation by LINE-1 were investigated. Results revealed a dose-dependent counteracting effect of vitamin E on H2 O2 -induced oxidative stress. Thereby, 10 μ M vitamin E proved to be more efficient than did 50 μ M in reducing MDA. Further, an induction of MLH1 and DNMT1 gene expression was noticed, accompanied by an increase in global methylation. Whether LINE-1 hypomethylation is a cause or effect of oxidative stress is still unclear. In conclusion, supplementation of exogenous antioxidants like vitamin E in vitro exhibits beneficial effects concerning oxidative stress as well as epigenetic regulation involved in DNA repair.